PEMANFAATAN BUKU TEKS IPS UNTUK MENGEMBANGKAN KETERAMPILAN MENYIMAK SISWA (Penelitian Tindakan Kelas Di Kelas VII-F Sekolah Menengah Pertama Negeri 13 Bandung) - dan Wawan Darmawan, Lina Hasanah (Universitas Pendidikan Indonesia, 2016)
This article is the result of a Classroom Action Research is motivated by the observation in the previous class to use textbooks IPS is not optimal, especially if associated with literacy school culture that is still far from expectations. The problem studied much more emphasis on